POWER OF THE RUSSIAN MONARCH:: ON THE QUESTION OF CIVILIZATIONAL AND CULTURAL IDENTITY OF ITS LEGAL NATURE - Shairian, Georii (Revista Gênero e Interdisciplinaridade, 2020)
The study analyzes the legal nature of the tsar's power as a result of a long civilizational and cultural genesis of the Russian statehood with its source and fundamental features. There are four of them: succession autocracy, legal unlimitedness, tsar’s supremacy and sanctity. The study of the proposed problem takes into account the opinions of foreign and Russian authors, who laid the methodological foundations for the study of Russia as a kind of cultural and historical type with it own unique features. Each of these features describes the special aspects of tsar’s power, preserving it as a whole, since the diminution of any of its properties leads to the loss of understanding the tsar’s power as a legal phenomenon, significantly different from any other versions of the supreme power. The study involves many foreign and Russian authors, who formed the methodological basis of research in Russia as a kind of cultural and historical type, which has its own unique features that persist today.